2018
DOI: 10.1016/j.ijid.2017.10.020
|View full text |Cite
|
Sign up to set email alerts
|

HIV drug resistance following a decade of the free antiretroviral therapy programme in India: A review

Abstract: Although the overall burden of resistance against first-line ART agents remained steady over the study decade, periodic monitoring is essential. There is the need to develop an HIV-1 subtype C-specific resistance database in India.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 46 publications
(33 reference statements)
0
12
0
Order By: Relevance
“…The increasing and preferential usage of TDF in the clinical practice [ 21 ], including in a context of a failing regimen, could be the primordial reason for the significant expansion of K65R as other studies show a higher prevalence of this mutation in patients failing ART treatment [ 15 , 52 , 53 , 54 , 55 ]. However, although an increasing trend was identified in a cohort from India [ 56 ], several studies report a decrease on K65R levels over the years in other countries [ 48 , 57 , 58 , 59 , 60 ]. Reinheimer and colleagues suggest that the decline on K65R prevalence rates is linked with the increasing usage of single tablet ART regimens and the inclusion of AZT on the used treatment regimen, which has been liked with K65R development suppression [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…The increasing and preferential usage of TDF in the clinical practice [ 21 ], including in a context of a failing regimen, could be the primordial reason for the significant expansion of K65R as other studies show a higher prevalence of this mutation in patients failing ART treatment [ 15 , 52 , 53 , 54 , 55 ]. However, although an increasing trend was identified in a cohort from India [ 56 ], several studies report a decrease on K65R levels over the years in other countries [ 48 , 57 , 58 , 59 , 60 ]. Reinheimer and colleagues suggest that the decline on K65R prevalence rates is linked with the increasing usage of single tablet ART regimens and the inclusion of AZT on the used treatment regimen, which has been liked with K65R development suppression [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Failure to attain the required adherence level results in poorer prognosis, higher morbidity, mortality and the development of resistance to ART ( Iacob, Iacob & Jugulete, 2017 ; Nachega et al, 2011 ). Once resistance develops, it has dire consequences for individual PLWHA, family, community, healthcare providers and the healthcare system because treating ART resistant HIV strain requires second-line ART regimens, that are more expensive and have worse side effects ( Chauhan et al, 2019 ; Karade et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Responses are reported on a Likert-scale ranging from 0 "Not at all" to 3 "Most of the time" and reverse coded for negatively-framed items. The HADS-D has four scoring levels generated based on the sum of the responses: none [0-7], mild [8][9][10], moderate [11][12][13][14], and severe [15+]. One pilot study with PLH for the current study using this measure found high rates of depression but low rates of anxiety (26).…”
Section: Methodsmentioning
confidence: 99%
“…HIV requires lifelong self-management to remain adherent. Low adherence and interruptions can lead to viral rebound and negative consequences including transmission to others (8,9), failure of and potentially resistance to firstline medication (10), and HIV disease progression (4). Improving and sustaining ART adherence is essential to both prevention and treatment outcomes.…”
Section: Introductionmentioning
confidence: 99%